ASEAN Energy Market Integration and Indonesia's Policy to Address Energy Poverty: Convergence or Divergence? - Anggraeni, Silvia Dian; Rudiany, Novita Putri; Putri, Ardila; Fitria, Naeli; Danastri, Hardhana Dinaring; Putri Dewi, Tiara Amima (KnE Social Sciences, 2022)
Access to modern energy among Association of Southeast Asian Nations (ASEAN) member countries has not been evenly distributed and some member countries are still in a status of energy poverty. Therefore, ASEAN has initiated the integration of energy markets. Indonesia is one of the ASEAN countries that still needs to overcome the problem of inequality in access to energy, especially in remote, isolated, underdeveloped, rural and border areas. ASEAN Energy Market Integration (AEMI) is based on the logic that integration of energy markets would allow national governments to address energy policy challenges more effectively and efficiently than they are able to do on their own; it therefore emphasizes interconnectivity through trade and energy investment. This study analyzed the linkage between the points of agreement in AEMI and the implementation of Indonesian policies in the context of harmonization of regulations, development of energy infrastructure, and subsidy policies. Using qualitative research methods, this study sought to rationalize whether the linkage between AEMI and Indonesian policies was convergent or divergent. This study concluded that there was a convergence between the AEMI agreement and the implementation of policies in Indonesia to address energy poverty. Keywords: AEMI, energy poverty, Indonesia, policy, electrification, new and renewable energy